Translation Techniques in the Translation of Figurative Languange in “It Ends with Us” - Adila, Nuril; Hilman, Evert H. (Asosiasi Ide Bahasa Kepri, 2024)
This research is aimed to find out the translation strategies used in the translation of figurative language items in the novel “It Ends with Us” by Colleen Hoover and its translated version “Akhir di Antara Kita.” This research uses a descriptive qualitative method, utilizing purposive sampling. Chesterman’s “Memes of Translation” is the main theory and also some other related theories utilized to analyse the data. The researcher focuses on three kinds of figurative language which were similes, metaphors and idiomatic pharasal verb. From 6 data, it is found that there were 2 similes, 2 metaphors, and 2 phrasal verb. The most translation technique that researcher found is Trope Change.